Oculus space lab impact on chemistry learning in PrepaTec students - Ramírez Gallegos, Eyra Nidia; Villalba Almendra, Lilia de Jesús; Sosa García, Ofelia; Reyes Izquierdo, Leticia; Arellano Blas, Laura del Carmen; López Botello, Cynthia Karyna (Frontiers in Education, 2025)
IntroductionDuring the Covid-19 pandemic, more than 27,000 students enrolled in high school at Tecnologico de Monterrey did not perform face-to-face laboratory practices, so it was not possible to objectively demonstrate the development and strengthening of their learning and the acquisition of scientific skills involved in practical work. This research work revolves around evaluating a tool in which the student can perform laboratory practices using immersive virtual reality.ObjectiveTherefore, the objective of the experiment was to measure the impact of laboratory practices using immersive virtual reality on learning and academic performance.MethodsThis study used a quantitative approach, with a control group and an experimental group to which a pre-test and post-test were applied. The sampling technique was non-probabilistic by convenience. To analyze the data we applied descriptive and inferential statistics using Shapiro-Wilk to test normality and Wilcoxon signed-rank test for non-parametric data. The sample consisted of 29 students from PrepaTec Campus Cuernavaca, who took science courses during the summer period of 2023, the ages of the participants ranged between 16 and 18 years old.ResultsThe results indicate that significant differences were found between the control and experimental groups of the practices. A significant difference was observed in the control group in lab 0, while positive trends were found in the experimental group in lab 1.DiscussionThe results of this study suggest that the implementation of virtual reality to perform laboratory practices has potential, but its effectiveness depends on several factors, including the training of students in the use of augmented realities, the pedagogical design of the intervention, and the adaptation time required.